Vom Bancor zum Euro: Und weiter zum Intor? - Heinz Handler (Austrian Institute of Economic Research (WIFO), 2008)
– The current paper analyses the similarities between the Bretton Woods system (BWS) and the Eurozone and looks into the future of the world monetary system. The gold standard, the Keynes Plan and the White Plan are identified as the most important sources of ideas that formed the BWS. Although Keynes was not particularly successful in Bretton Woods, his plan played a decisive role later on in the critique of the BWS as well as in the design of the European Monetary System. Either system was based on the concept of fixed exchange rates which were seen as more apt for international economic relations than flexible rates. In the BWS, fixed rates were seen to be achieved by coordinating economic policies of member states and by sporadic realignments of exchange rates. In the Eurozone, only policy coordination is available to fulfil this function. The favourable experience made so far with the euro may be utilised for monetary integration in other parts of the world. The Eurozone is also considered good practice for any reform of the international monetary system. Given the diverging political and economic goals of the major currency blocks, it may be questioned, however, whether the success of the euro also furthers the idea of developing a single world currency.
Keywords: 330; Gold standard; Bretton Woods system; European monetary integration; future of the international monetary system; Europäisches Wärhungssystem; Bretton-Woods-System; Vergleich; Eurozone; EU-Staaten; Internationales Währungssystem; Reform; Welt